2014
DOI: 10.1371/journal.pone.0087556
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis in Venom Gland of the Predatory Giant Ant Dinoponera quadriceps: Insights into the Polypeptide Toxin Arsenal of Hymenopterans

Abstract: Background Dinoponera quadriceps is a predatory giant ant that inhabits the Neotropical region and subdues its prey (insects) with stings that deliver a toxic cocktail of molecules. Human accidents occasionally occur and cause local pain and systemic symptoms. A comprehensive study of the D. quadriceps venom gland transcriptome is required to advance our knowledge about the toxin repertoire of the giant ant venom and to understand the physiopathological basis of Hymenoptera envenomation.ResultsWe conducted a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 81 publications
7
80
0
2
Order By: Relevance
“…The recent transcriptome analysis of the venom glands of the ant Dinoponera quadriceps (Ponerinae) has confirmed the presence and sequence of the first ICK-like peptide in ant venoms (Torres et al, 2014). This Dinoponera ICK-like peptide is a minor component of the venom of Dinoponera quadriceps but has a VI/VII cysteine framework (eCeCeCCeCeCe) consistent with other ICK toxins (Fig.…”
Section: Dinoponera Ick-like Toxinmentioning
confidence: 58%
See 1 more Smart Citation
“…The recent transcriptome analysis of the venom glands of the ant Dinoponera quadriceps (Ponerinae) has confirmed the presence and sequence of the first ICK-like peptide in ant venoms (Torres et al, 2014). This Dinoponera ICK-like peptide is a minor component of the venom of Dinoponera quadriceps but has a VI/VII cysteine framework (eCeCeCCeCeCe) consistent with other ICK toxins (Fig.…”
Section: Dinoponera Ick-like Toxinmentioning
confidence: 58%
“…However, proteinaceous venoms remain highly understudied despite the fact that they appear to be very common in both the Poneroid and Formicoid clades of ant venoms. Thus, venoms from Poneroid ants have been shown to be rich in peptides especially venoms from the subfamilies Ponerinae (Cologna et al, 2013;Johnson et al, 2010;Torres et al, 2014;Touchard et al, 2014a) and Paraponerinae (Piek et al, 1991a(Piek et al, , 1991bRykaczewska-Czerwinska et al, 2008). Peptides have also been characterized from the venoms of Formicoid ants belonging to the subfamilies Myrmicinae (Bouzid et al, 2013;Rifflet et al, 2012), Myrmeciinae (Davies et al, 2004;Inagaki et al, 2004Inagaki et al, , 2008aLewis et al, 1968;Mackintosh et al, 1998;Wiese et al, 2006;Wu et al, 1998), Pseudomyrmecinae (Touchard et al, 2014b) and Ectatomminae Nolde et al, 1995;Pluzhnikov et al, 1999).…”
Section: Ant Venom Peptidesmentioning
confidence: 99%
“…In particular, the inhibitor cystine knot (ICK) structural motif is relatively common in small cysteine‐rich peptide toxins from a variety of animal venoms and plants . While large numbers of ICK peptide toxins have been reported in other arthropods such as cone snails, sea anemones, spiders and scorpions, only two such ant venom peptides with a disulfide connectivity consistent with ICK toxins have been described: a Dinoponera ICK‐like peptide and SKTXs . Indeed, all the disulfide‐rich peptides previously isolated from ant venoms were homo‐ and heterodimeric complexes such as the myrmexins, pilosulins, and ectatomins found in venoms from the subfamilies Myrmeciinae, Pseudomyrmecinae and Ectatomminae (for a complete review, see Aili et al …”
mentioning
confidence: 99%
“…Recently, our group produced a D. quadriceps venom gland cDNA library to investigate the toxin repertoire in the venom used in this work. It was observed that dinoponeratoxins are major components, but also peptides pilosulin-like were found, and these peptides reported primarily for its antimicrobial effect (Torres et al 2014). However, these antimicrobial peptides have been subjected to further analysis and molecular modelling in order to reduce its toxic effects, such as the pilosulins (Zelezetsky et al 2005).…”
Section: Discussionmentioning
confidence: 99%